Pertunjukan Wayang Kulit Nang Talung, Representasi Kehidupan Masyarakat Thailand Selatan - Tanudjaja, Bing Bedjo (Institute of Research and Community Outreach - Petra Christian University, 2012)
Nang Talung shadow puppet performance in southern Thailand is one of the shadow puppet performances in Thailand. The development of the figure, the creation and presentation techniques as well as the story underwent evolution according to the times and technological developments. Nang Talung puppet show is a representation of a growing phenomenon in the life of Thai society in general and especially the community of South Thailand.